2012
DOI: 10.1089/lap.2012.0198
|View full text |Cite
|
Sign up to set email alerts
|

Complete Endoscopic Closure (Clipping) of a Large Esophageal Perforation After Pneumatic Dilation in a Patient with Achalasia

Abstract: The risk of esophageal perforation following endoscopic balloon dilation for achalasia is in the range of 1%-5%, with a mortality rate of 1%-20%. Perforations need to be recognized early, and, if reasonable, an immediate endoscopic repair should be pursued quickly. Herein, we report a case of successful endoscopic closure by clipping of a large iatrogenic perforation in a patient with achalasia. An 80-year-old woman with achalasia was admitted to our institution to undergo pneumatic dilation. A 40-mm balloon d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…In the first one, Huang et al reported four patients with large esophageal perforations secondary to endoscopic retrograde cholangiopancreatography (ERCP) probes. In the second case report, esophageal perforation occurred during pneumatic dilation in a patient with achalasia . In the third case report, perforation occurred because of endoscopic management of food impaction in the upper esophagus .…”
Section: Resultsmentioning
confidence: 93%
“…In the first one, Huang et al reported four patients with large esophageal perforations secondary to endoscopic retrograde cholangiopancreatography (ERCP) probes. In the second case report, esophageal perforation occurred during pneumatic dilation in a patient with achalasia . In the third case report, perforation occurred because of endoscopic management of food impaction in the upper esophagus .…”
Section: Resultsmentioning
confidence: 93%
“…Acute perforations are potentially life-threatening emergencies in which prompt closure is required to avoid contamination of visceral spaces [13]. The management of patients with esophageal perforation following esophageal dilation depends upon the severity of the perforation and the elapsed time between the perforation and the diagnosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…As this method is new, there is limited data on the successful use of clips for the closure of esophageal perforation. [22][23][24] Over-The-Scope Clips (OTSC)…”
Section: Through-the-scope (Tts) Clipsmentioning
confidence: 99%